2020
DOI: 10.21203/rs.3.rs-39317/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of the Effect of Pyridoxine Hydrochloride Supplementation on Anthropometric Measurements, Body Composition, Visceral Adiposity Index and Metabolic Status in Obese and Overweight Women

Abstract: Abstract Background and Objectives: Obesity has reached epidemic proportions globally. Among several methods for treating obesity, the use of dietary supplements is common recently. One supplement that can help in this regard might be vitamin B6 in high doses.The objective of this study was to evaluate the efficacy of pyridoxine hydrochloride supplementation on anthropometric measurements, body composition, visceral adiposity index and metabolic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Previous studies have found that pyridoxine supplementation can effectively raise PLP levels in this population (24,37). A study found that supplementation significantly increased PLP levels compared to placebo, suggesting that pyridoxine supplementation 150 mg/day for 4 months can effectively raise PLP levels (24.25 nmol/L to 156.25 nmol/L) (38) (33). The result of current study (23.14 nmol/L to 40.77 nmol/L) in agreement with previous study.…”
Section: Effect Of Restoration Of Endogenous Pyridoxine (Plp)supporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies have found that pyridoxine supplementation can effectively raise PLP levels in this population (24,37). A study found that supplementation significantly increased PLP levels compared to placebo, suggesting that pyridoxine supplementation 150 mg/day for 4 months can effectively raise PLP levels (24.25 nmol/L to 156.25 nmol/L) (38) (33). The result of current study (23.14 nmol/L to 40.77 nmol/L) in agreement with previous study.…”
Section: Effect Of Restoration Of Endogenous Pyridoxine (Plp)supporting
confidence: 90%
“…Some studies included participants with a positive family history of diabetes, indicating a genetic predisposition to the disease. This allowed researchers to explore whether the effects of pyridoxine on glycemic status, BMI, metabolic activity, lipid profile, and oxidative stress in T2DM may vary in individuals with a familial risk compared to those without such a history (33,34). The duration of morbidity with T2DM, referring to the length of time since the initial diagnosis, has been a crucial characteristic in previous studies.…”
Section: Demographics and Characteristics Of Participantsmentioning
confidence: 99%